Мовленнєвий акт вибачення в німецькомовному розмовному дискурсі - Герасимов, Тарас Олександрович; Herasymov, T. O. (Харків : Харківський національний університет імені В. Н. Каразіна, 2024)
The life and activities of society are impossible without communication between people, as it is a necessary condition for any activity. The process of communication largely determines well-being, effectiveness of actions, mood of people, etc. Often in everyday speech, and sometimes even in scientific literature, speaking and communication are used interchangeably. However, the concepts of "speaking" and "communication" differ from each other. The concept of "communication" is more general, and "speaking" is specific, denoting only one of the types of communication. The process of communication is important in the lives of people all over the world and represents the exchange of any information between the addresser and the addressee. This process consists of a number of purposeful communicative acts, which are implemented by communicators in specific communicative situations. It is communication that is the main object of study in pragmalinguistics. The apologetic speech act can be confidently attributed to such acts. This work is devoted to establishing the pragmalinguistic features of the apology in the German language. Apology is one of the most frequent speech acts in most cultures, and it carries important and interesting information for pragmalinguistic research. The results we can obtain from the analysis of apology as a speech act are particularly valuable for understanding the linguistic culture of German-speaking countries. In modern pragmalinguistics, different types of speech acts are studied depending on their illocutionary force: greeting, advice, appeal, compliment, order, irony, offer and refusal, jealousy and envy, and others. From the standpoint of pragmalinguistics, we consider it appropriate to consider the speech act of apology as a hybrid speech act. Speech acts of apology (a hybrid of expressive and directive) are studied as hybrids, as well as warnings (a hybrid of directive and assertive) and threats (a hybrid of directive and commissive) justification (a hybrid of assertive and expressive), certification (a hybrid of assertive and expressive), offering a service (hybrid quisitive and commissive). This work will substantiate the hybrid illocutionary status of the speech act of apology
Speech act of apology in German spoken discourse
Науковий керівник - Безугла Лілія Ростиславівна, доктор філологічних наук, професор, професор кафедри романо-германської філології
Keywords: HUMANITIES and RELIGION; прагматика; мовленнєвий акт; лексико-синтаксичні засоби; дискурс; перлокутивний